The effect of pacifier sucking on orofacial structures: a systematic literature review - Karin Michèle Schmid; Remo Kugler; Prasad Nalabothu; Carles Bosch; Carlalberta Verna (SpringerOpen, 2018)
Abstract Background Non-nutritive sucking habits may adversely affect the orofacial complex. This systematic literature review aimed to find scientific evidence on the effect of pacifier sucking on orofacial structures. Methods A search on MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science databases was conducted to find all pertinent articles published from inception until February 2018, based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The quality of the studies was evaluated using the risk of bias judgements in non-randomized studies of interventions (ROBINS-I). Results Among the 2288 articles found, 17 articles met the selection criteria: seven prospective cohort studies, nine cross-sectional studies, and one randomized clinical trial. Using ROBINS-I, 12 studies were evaluated to have a serious overall risk of bias and five, a moderate one. These studies claimed a strong association between a pacifier sucking habit and the presence of an anterior open bite and posterior crossbite. Functional/orthodontic pacifiers were shown to cause significantly less open bites than the conventional ones. Conclusions High level of evidence of the effect of sucking habits on orofacial structures is missing. The available studies show severe or moderate risk of bias; hence, the findings in the literature need to be very carefully evaluated. There is moderate evidence that the use of pacifier is associated with anterior open bite and posterior crossbite, thus affecting the harmonious development of orofacial structures. Functional/orthodontic pacifiers reduce the prevalence of open bite when compared to the conventional ones, but evidence is needed concerning the effects on posterior crossbite. Well-designed randomized controlled trials are needed to further analyze the effects of functional/orthodontic and conventional pacifiers on orofacial structures.